The Effectiveness of Using Telenursing in Supporting Patient Adherence to Antimalarial Medication - Diana Tati Haryati; Syamsul Anwar; Siti Badriah (Jurnal Penelitian Pendidikan IPA, 2024)
Malaria, which is still endemic in Papua Indonesia, especially Mimika Regency, has the classic issue of low adherence to antimalarial medication necessitates the use of a technological approach through telenursing, which includes reminders and self-reporting, allowing for optimal monitoring of adherence. To determine the effect of web application-based telenursing on adherence to antimalarial medication. This study used a quasi-experimental design with a pre-post test only approach. The instrument used was the Morisky Medication Adherence Scale-8 (MMAS). The sample consisted of 42 respondents per group. The analysis of medication adherence showed a significant difference between pre- and post-treatment in the intervention group, with a p-value of 0.000 (p-value < 0.05). Additionally, post-hoc pairwise comparisons showed that in the control group, a significant p-value of 0.000 was only found between day 15 and day 3, while in the intervention group, significant p-values ​​of 0.000 were found at every time point. Web application-based telenursing has been proven to significantly affect adherence to antimalarial medication.